The Relationship Between Parental Knowledge and Adolescent Delinquency: a Longitudinal Study - Stavrinides, Panayiotis (International Journal about Parents in Education, 2023)
The purpose of the present study was to test the direction of effect in the relationship between parents’ sources of knowledge (parental monitoring and child disclosure) and adolescents’ delinquency. The participants were 157 8th and 9th grade students and their mothers, randomly selected from urban and rural areas in Cyprus. A six-month, two-timepoint longitudinal design was used in which adolescents completed the delinquency scale while mothers completed the parental knowledge questionnaire. The results of this study showed that child disclosure at Time 1 predicted a decrease in both major and minor delinquency at Time 2 whereas adolescent major delinquency at Time 1 predicted a decrease in child disclosure and parental monitoring at Time 2. Contrary to previous wide-held assumption, parental monitoring at Time 1 did not significantly predict a decrease in delinquency at Time 2.